Customary Practices in African Print Fabric Design Process in the Nigerian Textile Industry - Adeloye, Adebayo Abiodun; Ogunduyile, Sunday Roberts; Akinbogun, Tolulope Lawrence (SCHOLARS: Journal of Arts & Humanities, 2022)
African print fabrics is commonly referred to as Ankara fabrics. It is a major textile product produced in Nigeria, which has the high economic value. This study focused on the customary practices in the African print fabric design process in the Nigerian textile industry. The study adopted survey research design. The population of the study comprised of African print fabric designers in the functioning textile companies in Nigeria. Ten African print fabric designers were sampled. Questionnaires and interviews were used for data collection. The data collected was analyzed using descriptive statistical tools. The study revealed that textile companies in Nigeria do not have value for quality designers, intellectual property right and originality of designs. It was recommended that the design institutes and professional design bodies should intervene in the design process in the Nigerian textile industry so as to generate designs that are original and capable of promoting the Nigerian textile industry.